Effect of perinatal depression on birth and infant health outcomes: a systematic review and meta-analysis of observational studies from Africa - Abel Fekadu Dadi; Temesgen Yihunie Akalu; Haileab Fekadu Wolde; Adhanom Gebreegziabher Baraki (BMC, 2022)
Abstract Background Antenatal depression is associated with intrauterine growth retardation, preterm birth, and low birth weight. Infants born to mothers with postnatal depression also may suffer from malnutrition and other health problems. Even though there are few single studies conducted so far, a systematic review of these studies is highly important to highlight the effect of antenatal and perinatal depression on adverse birth and infant health outcomes in Africa. Methods We used the Preferred Report Items for Systematic Review and Meta-analysis (PRISMA) when conducting this study. Databases like CINAHL (EBSCO), MEDLINE (via Ovid and PubMed), PsycINFO, Emcare, Psychiatry Online, and Scopus were searched. In addition, Google Scholar and references from a list of eligible studies were explored. We included good quality observational studies based on Newcastle Ottawa Scale which are published in the English language between 2007 and 2018.  Heterogeneity and publication bias were assessed. Meta-analysis with a random effect model was employed to determine the pooled effect sizes with a 95% confidence interval. The review protocol is registered in PROSPERO (CRD42018106714). Result We found three studies (1511 participants) and 11 studies (22,254 participants) conducted on the effect of antenatal depression on birth outcomes and perinatal depression on adverse infant health outcomes, respectively. The overall risk of having adverse birth outcomes was 2.26 (95% CI: 1.43, 3.58) times higher among pregnant mothers with depression. The risk of preterm birth and low birth weight was 1.77 (95% CI: 1.03, 3.04) and 2.98 (95% CI: 1.60, 5.55) respectively. Similarly, the risk of having adverse infant health outcomes namely malnutrition and febrile illness was 1.61 (95% CI: 1.34, 1.95) times higher among mothers who had perinatal depression. Conclusions We have found a significant association between antenatal depression and adverse birth outcomes, low birth weight and preterm birth. Similarly, a significant effect of perinatal depression on adverse infant health outcomes namely, malnutrition, and febrile illnesses was observed. The findings highlight that it is time to integrate mental health services with routine maternal health care services to improve birth outcomes and reduce infant morbidity.